Antioxidant and Anti-tyrosinase Activities of Aloe vera Rind and Gel Extracts - Sonya Bonifacia Mahadi; Rr. Anisa Siwianti Handayani; Wahyu Widowati; Wilsen Wilsen; Yunita Dewani; Edy Fachrial; I Nyoman Ehrich Lister (Global Medical & Health Communication (GMHC), 2019)
Aging is a natural process in human that can be characterized by the appearance of black spot on the skin due to hyperpigmentation. Aging may occur due to an excessive amount of free radicals in the body. Antioxidants possess ability to capture free radicals and inhibit tyrosinase which induces skin aging. Aloe vera has been used in traditional medicine because it contains several bioactive compounds that act as antioxidant and prevent aging process. This study aims to determine phytochemical content, antioxidant activity and tyrosinase inhibition activity of Aloe vera rind (AVRE) and gel (AVGE) extract. This research was carried out at the laboratorium of Aretha Medika Utama-Biomolecular and Biomedical Research Center in Bandung city in September–November 2018. Phytochemical assay was determined using modified Farnsworth method. Antioxidant assay was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and antiaging assay was obtained using tyrosinase inhibition assay. AVRE contains flavonoid, phenol, steroid, and alkaloid. Meanwhile, AVGE contains steroid and alkaloid. IC50 DPPH scavenging activity of AVRE was 113.18 µg/mL followed by AVGE was 291.96 µg/mL. IC50 tyrosinase inhibition activity of AVRE was 65.04 µg/mL followed by AVGE was 111.89 µg/mL. AVRE had more active DPPH scavenging activity and tyrosinase inhibition activity than AVGE. AKTIVITAS ANTIOKSIDAN DAN ANTITIROSINASE KULIT DAN DAGING LIDAH BUAYA (ALOE VERA)Penuaan merupakan proses alamiah pada manusia. Penuaan dapat terjadi akibat kadar radikal bebas yang tinggi di dalam tubuh. Antioksidan memiliki kemampuan memerangkap radikal bebas dan menghambat kerja enzim yang berperan dalam proses penuaan. Lidah buaya (Aloe vera) telah digunakan dalam pengobatan tradisional karena diketahui mengandung senyawa bioaktif yang bermanfaat dalam menangkal radikal bebas dan menghambat penuaan. Penelitian ini bertujuan mengetahui kandungan fitokimia dalam ekstrak etanol kulit lidah buaya (EKLB) dan ekstrak etanol daging lidah buaya (EDLB), mengetahui aktivitas antioksidan, pemerangkapan 2,2-difenil-1-pikrilhidrazil (DPPH), serta aktivitas antitirosinase EKLB dan EDLB. Penelitian ini dilakukan pada September–November 2018 di laboratorium Aretha Medika Utama Biomolecular and Biomedical Research Center (BBRC). Analisis fitokimia dilakukan menggunakan metode Farnsworth yang dimodifikasi. Aktivitas antioksidan dianalisis menggunakan metode pemerangkapan DPPH, sementara uji antipenuaan dilakukan menggunakan metode uji aktivitas antitirosinase. Hasil uji fitokimia menunjukkan EKLB mengandung flavonoid, fenol, steroid, dan alkaloid; sedangkan EDLB mengandung senyawa steroid dan alkaloid. EKLB dan EDLB memiliki aktivitas pemerangkapan DPPH dengan nilai IC50 secara berurutan 113,18 µg/mL dan 291,96 µg/mL. Penghambatan tirosinase EKLB dan EDLB dengan nilai IC50 secara berurutan 65,04 µg/mL dan 111,89 µg/mL. EKLB memiliki aktivitas antioksidan dan penghambatan tirosinase yang lebih baik dibanding dengan EDLB.